High CO2-mediated down-regulation of photosynthetic gene transcripts is caused by accelerated leaf senescence rather than sugar accumulation - Sonnewald, Uwe; et al. (Febs Letters, 2000)
The influence of elevated atmospheric CO2 on transcript levels of photosynthetic genes was investigated in leaves of Nicotiana tabacum cv. SamsunNN and cv. Wisconsin38 plants, Plants were grown under ambient (400 ppm) and elevated (800/1000 ppm) atmospheric CO2, and transcript levels were determined in leaves of different age. Down-regulation of photosynthetic gene transcripts,vas apparent in senescing leaves only. A correlation between transcript levels and leaf contents of soluble sugars could not be found, To investigate whether a shift in leaf ontogeny would be involved in the regulation of photosynthetic genes transgenic tobacco plants expressing either the gus or ipt gene under control of the senescence-specific SAG-12 promoter [Gan, S. and Amasino, R.M. (1995) Science 270, 1986-1988] were included in our studies, As expected SAG-12-driven GUS activity increased with leaf age. This increase of GUS activity was stimulated by elevated atmospheric CO2, accompanied by a loss of chlorophyll and the down-regulation of photosynthetic genes, verifying that high CO2 accelerates leaf ontogeny. Senescence as well as down-regulation of photosynthetic gents could he delayed by ipt expression. Levels of soluble sugars were indistinguishable front wild type or even slightly elevated in ipt transgenic plants, Therefore, sugar accumulation as a cause for down-regulation of photosynthetic genes under high CO2 can be excluded. It appears more likely that the high CO2-mediated decline in photosynthetic gene transcripts is due to a temporal shift in leaf ontogeny. (C) 2000 Federation of European Biochemical Societies, Published by Elsevier Science B.V. All rights reserved.
Keywords: carbon dioxide; photosynthetic gene; sugar regulation; senescence; transgenic plant; Nicotiana tabacum